2014
DOI: 10.1073/pnas.1411975111
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductivity of engineered cartilaginous templates devitalized by inducible apoptosis

Abstract: Significance It has been previously reported that hypertrophic cartilage tissues engineered from human mesenchymal stromal cells can efficiently remodel in vivo into bone organs, recapitulating developmental steps of endochondral ossification. We have here demonstrated that the extracellular matrix (ECM) of such engineered cartilage, even in the absence of a living cell component, retains frankly osteoinductive properties. The use of an apoptosis-driven devitalization technique revealed the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 38 publications
1
74
0
1
Order By: Relevance
“…ECM from various sources have been studied previously as biomaterials for tissue regeneration, as ECM has a number of obvious advantages for tissue engineering applications [17,35,43,44]. The data presented in this study add to the body of work demonstrating the utility of different cell and native tissue-derived ECM to be used as scaffolds in orthopaedic medicine [21,25,[45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ECM from various sources have been studied previously as biomaterials for tissue regeneration, as ECM has a number of obvious advantages for tissue engineering applications [17,35,43,44]. The data presented in this study add to the body of work demonstrating the utility of different cell and native tissue-derived ECM to be used as scaffolds in orthopaedic medicine [21,25,[45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies have demonstrated that ectopic bone formation within growth factor delivery scaffolds also occurs through this endochondral pathway [40]. In contrast, recent studies have suggested that bone formation induced by devitalized cartilaginous ECM cannot be defined as being of the endochondral origin [21]. Further work is required to track the fate of progenitor cells that are recruited into devitalized ECM derived scaffolds in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, implantation of a chondrogenic construct can spontaneously induce the subsequent formation of mineralized tissue, reminiscent of what is seen during endochondral bone formation (Harada et al, 2014;Tam et al, 2014;van Gastel et al, 2014;Weiss et al, 2012). Moreover, endochondral ossification can also be induced using cell-free implants obtained by devitalizing chondrogenic constructs, especially when matrix characteristics and the presence of growth factors to attract host cells are preserved (Bourgine et al, 2014). Furthermore, while the effect of hypoxia on osteogenic differentiation is not yet fully clear, the activation of hypoxia signalling in chondrocytes (Pfander et al, 2004) leads to higher expression of cartilage markers during in vitro culture (Shi et al, 2015;Strobel et al, 2010;Zhou et al, 2015), as well as improved collagen cross-linking during matrix synthesis (Makris et al, 2014) despite lowering of the proliferation of chondrocytes.…”
Section: Endochondral Bone Formation As a Physiological Adaptation Agmentioning
confidence: 99%